Kelayakan Air Yang Diminum Siswa-Siswi Di Madrasah Tsanawiyah Negeri 35 Jakarta - Vrio Andris; Rosalita; Robi Fadil Muhammad; Eny Rose; Murtasiah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Examination of the quality content of trademark AMDK by testing 16 trademarks of mineral and demineral water from canteens and shops or stalls located in the neighborhood around MTs.N 35 West Jakarta. The sampling technique uses purposive sampling by using testing 3 times per one selected AMDK brand which has a bottle of 500 – 600 ml with several criteria so that the results can be in accordance with the research objectives. The examination method is with a digital water quality test measuring device that has a multifunctionality for testing the content of pH, TDS, Temperature and Salt. The test results obtained the best 3 water TDS, namely the AMDK trademark with test sample code 09. 06, and 02. Test samples 10, 14, and 01 have the lowest TDS large 3 content. In the TDS test, 1 demineral water with TDS 3 content was obtained with a test sample code of 16. Mineral Water with a pH value which sequentially has the highest pH value is owned by the amdk trademark mineral water with test sample codes 15, 09, 13 and 06. the AMDK 16 trademark has a low pH value of 6.53 where this trademark is a demineral AMDK. Salt tests on 16 AMDK trademarks still meet the standard with a range of 0.02-0.04%.